Papillary carcinoma thyroid - A 11 year epidemiological study with histopathological correlation in a tertiary care centre in South Malabar Region in Kerala, India (Journal of Pathology of Nepal, 2015)
Background: Thyroid cancer is the commonest endocrine malignancy. Based on recent data, thyroid cancer is the fifth most common cancer in women. To our knowledge the  present study  is the first of its kind, correlating epidemiological and histomorphological data so as to assess the  major cause hypothesis for thyroid cancers, focusing more on  papillary  carcinoma and its variants, comparing it with each other and with other  thyroid carcinomas and also correlating with gender, life style and religion.Materials and methods: This study was conducted in the Department of Pathology, MES Medical College, Perinthalmanna, Kerala, India, from January 2004 to June 2015.Two thousand and fifty thyroidectomy cases were studied.Results: Out of the total 2050  cases, thyroid cancers constituted  295 (14.39%);  of which 10.1% (208 cases) were Papillary carcinoma thyroid (PCT) and its variants; 165 cases were seen in females (79.33%) and  the incidence in males were only 20.68% (43 cases).The commonest variant encountered was classical papillary carcinoma (113 cases, 54.32%).Conclusion: Our study of papillary thyroid carcino